Mobile Computing, Applications, and Services : c - Sigg, Stephan; Nurmi, Petteri; Salim, Flora; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 7th International Conference on Mobile Computing, Applications, and Services (MobiCASE 2015) held in Berlin, Germany, in November 2015. The 16 full and 4 poster papers were carefully reviewed and selected from 43 submissions, and are presented together with 4 papers from the First Workshop on Situation Recognition by Mining Temporal Information (SIREMETI 2015). The conference papers cover the following topics: intelligent caching, activity recognition and crowdsourcing, mobile frameworks, middleware, interactive applications and mobility.
Intelligent caching -- Activity recognition and crowdsourcing -- Mobile frameworks -- Middleware.-Interactive applications -- Mobility.
Keywords: Computer network architectures; Computer science; Computer Systems Organization and Communication Networks; Computer Applications; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Computers and Society